Drepanosticta machadoi spec. nov. from New Guinea (Odonata: Platystictidae) - Theischinger, G.; Richards, S. J. (Zootaxa, 2014)
Drepanosticta machadoi sp. nov. (Holotype ♂: Dablin Creek, Hindenburg Range) from Papua New Guinea is described. The new species is a predominantly black damselfly, the male with four pale/bright pattern elements on each side of the synthorax, dorsum of segments 9 and 10 largely bright blue, and a uniquely shaped posterior lobe of the pronotum which is a wide-angled fork with rather straight, narrow finger-like prongs. It is referred to the Drepanosticta conica group of species and a key to the males of the D. conica group is provided.